Analisis Perbandingan Metode SMART Dan MFEP Dalam Menentukan Driver Bus Terunggul Pada PT. Putra Pelangi Perkasa - Muhammad Fikri Riandra; Andre Hasudungan Lubis; Nurul Khairina (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
Human Resources (HR) in a transportation companies may affect many aspects that determine work success, especially the drivers. Competition among drivers is getting tougher, hence the companies face difficulties in finding the best bus drivers. Nevertheless, the assessment still uses the traditional method, namely by using a book as the calculation. The study used the Simple Multi-Attribute Rating Technique (SMART) and Multi Factor Evaluation Process (MFEP) methods to rank drivers’ performance in terms of discipline, knowledge, loyalty, and years of service. The system used in this study also compares the two methods with the actual rank from the company. The population in this study was 90 respondent, with a sample data of 10 drivers. The results show that the SMART method is closer to manual ranking, which has 7 similarities out of 10 ranking sequences or 70% accuracy rate with the manual calculations. On the other hand, only 4 similarities out of 10 ranking se-quences were generated by the MFEP method. Thus, the MFEP method only has a 40% accuracy rate with manual calculations. To sum up, the research created a decision support system that has certainty in choosing the best bus driver to assists the leaders to find the best driver to get an exclusive bus.